Electro-acupuncture for central obesity: randomized, patient-assessor blinded, sham-controlled clinical trial protocol - Linda L. D. Zhong; Xingyao Wu; Tsz Fung Lam; Ying Ping Wong; Peihua Cao; Emily Yen Wong; Shipping Zhang; Zhaoxiang Bian (BMC, 2021)
Abstract Background Obesity is a common medical condition. Among all the classifications of obesity, central obesity is considered to be a significant threat on the health of individuals. Scientific researches have demonstrated that the accumulation of intra-abdominal fat is associated with higher metabolic and cardiovascular disease risks independently from Body Mass Index (BMI). Our previous research found that the combination of electro-acupuncture and auricular acupressure could significantly reduce the body weight and the BMI compared to sham control group. Methods/design This is a patient-assessor blinded, randomized, sham-controlled clinical trial on electro-acupuncture for central obesity. One hundred sixty-eight participants with central obesity will be randomly assigned to two groups, which are the acupuncture group and the sham control group. The whole study duration will be 8-week treatment plus 8-week follow up. The primary outcome is the change in waist circumference before and after the treatment. The secondary outcomes include the changes in hip circumference, waist-to-hip circumference ratio, BMI and body fat percentage during the treatment and follow-up. Conclusion The trial will evaluate the efficacy and safety of electro-acupuncture for central obesity compared with sham acupuncture. The study may provide the solid evidence of electro-acupuncture on central obesity in Hong Kong. Trial registration ClinicalTrials.gov Identifier: NCT03815253 ,Registered 24 Jan 2019.